The Abu Bakr cemetery at Giza - Ḥandūsah, Tuḥfah Aḥmad; Brovarski, Edward (Wilbour studies in egyptology and assyriology, 2020)
"The present volume reflects the work of the joint expedition of Cairo University and Brown University to record and publish the tombs uncovered on behalf of Cairo University by Prof. Abdel-Moneim Abu Bakr from 1949 through 1953, but never published. The loss of field records and lack of a map of the site meant that new, salvage excavation had to be undertaken. A total of six seasons, from 2000-2006 resulted in the clearing, remapping, and recording of the monuments in the cemetery. Abu Bakr Cemetery is of particular interest because the majority of mastaba tombs belong to relatively low-ranking individuals. Thus they have the potential to she light on the social status of Egypt's working classes"--